Manajemen Kepala Sekolah Dalam Memperoleh Prestasi Budaya Literasi - Aryati Suparyana; Rejokirono Rejokirono (Media Manajemen Pendidikan, 2023)
The purpose of this study was to obtain a description of the principal's management analysis in obtaining literacy culture achievements at the national level at SD Negeri 4 Wates. This study used a descriptive qualitative approach. Data collected by interview, observation, and documentation. This research was conducted at SD Negeri 4 Wates. Data analysis was carried out by means of data reduction, data presentation, and conclusions as well as verifying data. Data validity by increasing persistence and using source, technique, and time triangulation. The results of the study show that the management of school principals in obtaining literacy culture achievements at the national level is carried out by planning, organizing, implementing, and evaluating or supervising which begins with a school strategic discussion (SSD).